The Effects of Positive Reinforcement on Students’ Writing Achievement in an Indonesian EFL Classroom - Saiful Gaffar; Haryanto Atmowardoyo; Syarifuddin Dollah (Har Press Indonesia, 2022)
This research was aimed to find out the effects of positive reinforcement on students’ writing achievement and the students’ perception about the implementation of positive reinforcement. This research design used a quasi-experimental design. A quasi-experimental design is the design of experiment that use two classes that were investigated. The concept of quasi-experimental design there were two groups, experiment class and control class. The total of sample were 48 students consisted of 24 students for experiment class and 24 students for control class and this research applied cluster random sampling. The instruments used were tests and questionnaires. The results of the research showed: (1) there was a significant effect of positive reinforcement on students’ writing achievement. (2) the students have positive perception about the implementation of positive reinforcement in teaching writing.